2016
DOI: 10.1007/978-3-319-29887-0_20
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Flow-Assisted Resection of Brain AVMs

Abstract: Multimodal flow-assisted approach in AVM surgery proved a feasible, safe, and reliable methodology to achieve AVM resection with high radicality and low morbidity rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…No flow signals could be obtained from the feeding vessels after surgical resection of the malformation in the first study, while a residual flow of the venous drainage was detected in 5 out of 27 cases (18.5%) described by Della Puppa [12] Two studies described iMDS employment in spinal dAVFs. Della Puppa and colleagues, 2016 [14] showed that blood flow in perimedullary venous plexus ranged from 2 to 12 mL/min (mean 8 mL/min). BFV always dropped lower than 1 mL/minute after temporary and definitive fistula occlusion by clip positioning and coagulating respectively, in all cases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No flow signals could be obtained from the feeding vessels after surgical resection of the malformation in the first study, while a residual flow of the venous drainage was detected in 5 out of 27 cases (18.5%) described by Della Puppa [12] Two studies described iMDS employment in spinal dAVFs. Della Puppa and colleagues, 2016 [14] showed that blood flow in perimedullary venous plexus ranged from 2 to 12 mL/min (mean 8 mL/min). BFV always dropped lower than 1 mL/minute after temporary and definitive fistula occlusion by clip positioning and coagulating respectively, in all cases.…”
Section: Resultsmentioning
confidence: 99%
“…In the present systematic review, two articles [7,14] reported the use of iMDS during cerebral AVMs surgery. Burkhardt et al [7] measured intraoperative flow using micro Doppler in a case series of 32 consecutive patients.…”
Section: Use Of Intraoperative Microdoppler Sonography In Arterio-ven...mentioning
confidence: 99%
See 1 more Smart Citation